Insecticide resistance of malaria mosquitoes from Guinea Conakry - Vezenegho, Samuel Bumuh (My University, 2009)
Introduction: There is only limited information on malaria vector species composition, vector status and susceptibility status in Guinea Conakry. This work provides more information from three localities (Boffa, Siguiri and Mount Nimba) with very different ecological settings. Methods: Anopheles mosquitoes were collected resting inside houses. Field bioassays were performed on An. gambiae s.l using the standard WHO protocol. Further species identification by PCR, laboratory bioassay by WHO standards, biochemical enzyme analysis, sporozoite ELISA, kdr detection by PCR and pyrosequencing were performed. Results: Of 600 specimens, 494 (82.3%) were An. gambiae and 2 (0.33%) An. arabiensis. Plasmodium infection rates varied from 1.25 to 5%. Resistance to 4% dieldrin and 0.1% bendiocarb need confirmation in Boffa and to 0.05% deltamethrin and 5% malathion in Siguiri. Resistance to DDT, dieldrin and bendiocarb occurred in Siguiri and Mount Nimba. F1 progeny of wild An. gambiae s.s exposed to pirimiphos methyl indicated elevated esterase and monooxygenase enzymes involved in metabolic detoxification of insecticides. The Kdr-w mutation is present in both the M and S forms of An. gambiae. Kdr genotypes by pyrosequencing and sequencing were in agreement but the standard PCR method gave 28% false positives. Conclusion: Both molecular forms of An. gambiae are implicated in malaria transmission, occur in sympatry and exhibit some degree of resistance to insecticides at all localities. The mechanism of resistance is unclear. Pyrosequencing is more accurate for detecting kdr than the standard PCR method. Vector control interventions need to be tailored to each site based on the data collected by on-going monitoring and surveillance.